Durability of treatment effects following internet‐delivered cognitive behavioural therapy for depression and anxiety delivered within a routine care setting. (26th April 2022) - Palacios, Jorge E.; Enrique, Angel; Mooney, Olwyn; Farrell, Simon; Earley, Caroline; Duffy, Daniel; Eilert, Nora; Harty, Siobhan; Timulak, Ladislav; Richards, Derek
Abstract: Objective: To investigate post‐treatment relapse and remission rates 3, 6 and 9 months after completion of an acute phase of a clinician‐supported internet‐delivered cognitive‐behavioural therapy (iCBT) for anxiety and depressive symptoms, within a routine care setting. Method: Secondary analysis from a 12‐month pragmatic randomized‐controlled trial delivered within the Improving Access to Psychological Therapies (IAPT) programme in England. Participants in the intervention arm were included if they met criteria for reliable recovery from depression (PHQ‐9) and anxiety (GAD‐7) at post‐treatment assessment. Survival analysis was used to assess durability of treatment effects and determine predictors to relapse at 3‐, 6‐ and 9‐month follow‐up. Hazard ratios predicting time‐to‐relapse were estimated with semi‐parametric Cox proportional hazards model. Results: Of the 241 participants in the intervention arm, 89 participants met the criteria for reliable recovery from depression and anxiety at the post‐treatment assessment. Of these 89 eligible cases, 29.2% relapsed within the 9‐month period, with 70.8% remaining in remission at 9 months post‐treatment. Of those who relapsed, 53.8% experienced a relapse of depression and anxiety; 7.7% experienced a relapse of depression only; and 38.4% experienced a relapse of anxiety only. Younger age, having a long‐term condition, and residual symptoms of anxiety at end‐of‐treatment were all significant predictors of relapse. Conclusions: This study is the first to explore the remission and relapse rates after an acute phase of iCBT treatment, within a routine, stepped‐care setting. The results add to the scarce literature on the durability of the effects of iCBT treatment in routine care settings, where patients are not typically followed up after receiving a completed course of treatment.